Observing our commitment to addressing gender based violence and reproductive rights in Uganda - Uganda Women’s Network (Uganda Women’s Network, 2010)
This brief is drawn from the concluding observations of the Committee on the convention on the Elimination of All Form the Discrimination Against Women (CEDAW) based on the combined fourth, fifth, sixth and seventh report of Uganda (CEDAW/C/UGA/4-7). It is intended to highlight the Committee’s specific concluding observations and recommendations on gender based violence (GBV) and reproductive rights (RR) so as to draw policy attention and action. Uganda ratified CEDAW in 1985.